Copyrolysed C3N4‐Ag/ZnO Ternary Heterostructure Systems for Enhanced Adsorption and Photocatalytic Degradation of Tetracycline. Issue 31 (27th September 2016) - Panneri, Suyana; Ganguly, Priyanka; Nair, Balagopal N.; Mohamed, Abdul Azeez Peer; Warrier, Krishna Gopakumar; Hareesh, Unnikrishnan Nair. S.
Abstract : The graphitic carbon nitride (g‐C3 N4 ) Ag/ZnO (CAZ) nanocomposite heterostructure was prepared by the copyrolysis of a precursor mixture containing melamine and nitrates of zinc and silver. This one‐pot synthetic approach facilitated the incorporation of fine dispersions of Ag and ZnO on C3 N4 sheets. The CAZ sample thus prepared exhibited higher adsorption capacity and enhanced sunlight‐induced photocatalytic activity towards tetracycline degradation when compared with compositions of g‐C3 N4 ‐Ag, g‐C3 N4 ‐ZnO, ZnO‐Ag, and g‐C3 N4 . Incorporation of ZnO helped to utilize the UV component of sunlight, whereas ultrafine dispersions of Ag on the surface of the composite created intimate interfaces, facilitating the direct migration of photoinduced electrons to the Ag surface for an efficient separation of photogenerated electron‐hole pairs. The present work exemplifies a simple and convenient synthetic protocol for processing the tricomponent heterostructured system of g‐C3 N4 ‐Ag/ZnO for the effective degradation of pollutants such as tetracycline. Abstract : Combined adsorption and sunlight‐induced photocatalysis by C3 N4 ‐Ag‐ZnO ternary composites have been developed for the efficient degradation of tetracycline antibiotic.